2021
DOI: 10.4103/ijo.ijo_1269_20
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective measures of the patient experience before, during, and after intravitreal anti–vascular endothelial growth factor injections

Abstract: Purpose: To assess patient experience of intravitreal injections using vital-signs, visual-experience, pain-rating and emotional response during intravitreal anti-VEGF injections. Methods: A prospective observational study of patient experience of intravitreal anti-VEGF injections done following metrics were collected pre-injection, during injection, and post-injection: pain assessment using visual analog score, fear-response rating, visual-experience questionnaire, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In their report, concerns about treatment effectiveness were a main source of anxiety, comparable to our findings, that the majority of our patients are afraid of unfavourable results of the examination regarding disease activity. Mekala et al reported similar results about fear, but a higher number of patients feeling pain during and after the IVI than in our study [9]. In line with our results, pain was not associated with the time period since onset of treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In their report, concerns about treatment effectiveness were a main source of anxiety, comparable to our findings, that the majority of our patients are afraid of unfavourable results of the examination regarding disease activity. Mekala et al reported similar results about fear, but a higher number of patients feeling pain during and after the IVI than in our study [9]. In line with our results, pain was not associated with the time period since onset of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies focus on morphological and functional outcome parameters and do not include the perception of patients on the treatment strategy so that evidence on this complex topic is limited. Less is known about patient's experience undergoing anti-VEGF therapy [6][7][8][9].…”
Section: New Information In the Papermentioning
confidence: 99%